PENGARUH KUALITAS PELAYANAN, NILAI PELANGGAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN HOTEL SILIWANGI SEMARANG - Yulianta Restuadhi; Naili Farida; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2014)
Hospitality business competition in Semarang that  increase stringently insists bussinesmen in this service sector to improve their customers loyalty. In the midst of that condition there are Siliwangi Hotel’s customers that unsatisfied toward the service has been given. The purpose of this study to determine the influence of service quality and customer value toward the satisfaction of customer partially and in a combination, the influence of service quality, customer value, and customer satisfaction toward the loyalty of customer partially and in a combination. The number of samples in this study are 100 respondents. SPSS 16.0 version which is used for analyze validity, reliability and the influence between variables.                The results showed a positive and significant influence between service quality and customer value toward the satisfaction of customer partially, a positive and significant influence between service quality, customer value and customer satisfaction toward the loyalty of customer partially, the influence of service quality and customer value for a combination toward customer satisfaction, the influence of service quality, customer value and customer satisfaction for a combination toward customer loyalty.